Aplikasi E-Kohort Register Kesehatan Ibu Dan Anak (KIA) Pada Puskesmas Nosarara Kota Palu - Syahrullah Syahrullah (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2018)
This research was conducted based on empirical facts that occurred in the field, that maternal and child health services at the Nosarara Palu Health Center that were not supported by the use of information technology made maternal and child health care services not optimal, such as data errors, slow search, data redundancy and making reports that require a long time. One source of data to make reports on maternal and child health services in the Puskesmas was obtained from the results of MCH activities at the Puskesmas which were registered in a register called cohort (maternal health register and child health register. Therefore researchers made applications that could help midwives in service In the Puskesmas, this research was developed with a prototype method using Borland Dephi and MYSQL, before making the application a design test was conducted by interviewing 5 respondents.The results of this study obtained medical record data quickly and accurately, facilitating the midwife of the Nosarara health center in making cohort report participant service reports, facilitating midwives at the Nosarara health center in searching data for MCH patients, both new patients and older patients who frequently visit.